Experimental and Numerical Investigation of the Effect of Newly Tested Blades on the Aerodynamic Performance and Power Output of a Horizontal Axis Wind Turbine - (:unkn) unknown (My University, 2022)
There is no doubt that the effects of global warming are obvious for every human being on the Earth now. Therefore, the need to develop carbon dioxide-free sources of electricity is urgent. Wind Turbines are one of these most essential recently developed sources. For that reason, the University of Wisconsin-Milwaukee founded the wind tunnel lab., equipped with the state-of-the-art research tools, to take part in this procession.In chapter (3) of this thesis it is desired to investigate in detail the scenario that takes place behind a single wind turbine unit by focusing on three parameters; average axial wind velocity component, velocity deficit, and total turbulence intensity. The testing was done at mainstream velocity, U∞, of 5.2 m/s, u and v velocity components were captured by x-probe dual-sensor hot wire anemometer. A massive amount of point data was obtained, which then processed by a Matlab script to plot the desired contours through the successive transverse sections along the entire length of the test section. By monitoring the previously mentioned flow parameters, the regions of low velocity and high turbulence can be avoided while the location of the subsequent wind turbine is selected. The estimation of the distance, at which the inlet flow field will restore its original characteristics after being mixed through the rotor blades, is very important as this is the distance that should separate two successive turbines in an inline configuration wind farm to guarantee the optimum performance and to extract the maximum power out of the subsequent array of turbines. It is found that the hub height axial velocity recovery at six rotor diameters downstream distance is only 82%. This means that the power extraction out of the downstream turbine in an inline configuration wind farm is only 55% of the upstream turbine, if the same free stream velocity and blade design are adopted. Then, chapter (4) sheds light on wind farm layout design, site evaluation, and power output prediction by performing modeling and the experimental tests of a wind tunnel test section including a single wind turbine model inside was created and validated against present experimental data of the same model. The Large Eddy Simulation (LES) was used as a numerical approach to model the Navier-Stokes equations. The computational domain was divided into two areas; rotational and stationary. The unsteady Rigid Body Motion (RBM) model was adopted to represent the rotor rotation accurately. It is concluded through this investigation, if the rotational speed control is adopted, that the wind velocity increase enhances the axial velocity recovery. Hence, the separation distance between two successive turbines decreases while maintaining the same level of power extraction. This way, we can optimize available site exploitation. After that, chapter (5) of this work tries to popularize the use of residential-scale wind turbines because the last few decades witnessed a great development for the large-scale wind turbines, while small-scale wind turbines didn’t grab the same amount of interest. On this track, four airfoils (GOE 447, GOE 446, NACA 6412 and NACA 64(3)-618) characterized by their high published lift-to-drag ratios (161.3, 148.7, 142.7 and 136.3 respectively) are used to generate an entire 7 m long blades for three-bladed rotor wind turbine models tested numerically at 12.5 m/s rated wind speed, with design tip speed ratio of 7. The criterion to judge each model’s performance is the power output. Thus, the blades of the model which produce the highest power are selected to undergo a leading-edge modification (tubercles), and a tip modification (winglet), seeking power improvement. Finally, the best basic model is tested at a spectrum of tip speed ratios (5 to 7.5, with 0.5 step) to find the optimum tip speed ratio. Moreover, chapter (6) highlights that Most of the available research work of horizontal axis wind turbines is focused on either lab-scale (15-60 cm rotor diameter) or commercial large-scale (80-130 m rotor diameter). There is a lack of published data on residential-scale turbines. The current work fills this gap because residential-scale turbines will be one of the key technologies during the next ten years since the current administration promotes dependence on renewables to cut carbon footprint. Therefore, the current work runs wind tunnel experimentation and performs 48 numerical simulations to evaluate the performance of a residential scale wind turbine with a blade generated from GOE 447 airfoil at three wind speeds (7.5, 12.5, and 17.5 m/s). Three different vortex generator designs were tested numerically when added on the suction side of a 7 m blade. Two of those designs produced more power than a baseline rotor does (7.2% and 10.9% more power than the baseline rotor were achieved at 12.5 m/s wind speed). Furthermore, three winglet designs were added to the baseline design to investigate their effect on power production. The 90o, 60o, and 30o cant angles produce 5.0%,7.9% and 6.9% more power than the baseline design, respectively. It was very important to investigate the effect of combining the most successful vortex generator and winglet design on the performance of a single blade. Combining both techniques impairs the functionality of each other, leading to a deteriorated overall performance and less power (generally 6% to 8% less power than the baseline design). Furthermore, chapter (7) utilizes wind tunnel experimentation and uses CFD simulations to evaluate the performance of a 14 m-rotor diameter residential scale wind turbine at three wind speeds (7.5, 12.5, and 17.5 m/s). The blades of the rotor baseline design are built using GOE 447 airfoil. Five different tubercle designs were applied to the blade’s leading edge. One of those designs produces more power than a baseline rotor, with an optimum power improvement of 5.5% achieved at 12.5 m/s wind speed. Furthermore, three winglet designs were added to the tip of baseline design to investigate their influence on the power production. The 90o, 60o and 30o cant angles produce 5.0%,7.9% and 6.9% more power than the baseline design, respectively, at 12.5 m/s. Moreover, it is vital to investigate the effect of integrating leading-edge tubercles with winglets, then evaluate the influence of the combination on the aerodynamic performance and power output of the turbine model. It is found that when combining both techniques on the same blade, the improvement mechanism associated with each of them interferes with the other, leading to poor overall performance and less power in the majority of the run simulations. Finally, chapter (8) highlights the topics that have potential for future work.